Analisis Spasial Terhadap Tingkat Kerawanan Banjir DAS Kenali Kecil Menggunakan Metode SNI 8197:2015 - Heri Muda Setiawan; Heri Junedi; Mohd Zuhdi (Universitas Batanghari Jambi, 2022)
Floods are the most common disasters in almost all places, including Indonesia and Jambi City in particular. Areas that are directly exposed to the threat of flooding are in the Watershed. Land conversion is one of the causes of flooding in the Kenali Kecil watershed. This study uses the standard SNI 8197:2015 regarding the Flood Hazard Mapping Method 1:50,000 and 1:25,000 scale. The approach used is landscape analysis, which emphasizes the process of forming natural systems on the earth's surface. This study aims to analyze and produce a map of the level of flood vulnerability in the Kenali Kecil watershed area. The data needed in this study are ten days of rainfall data, slope data and land cover data. Slope data was obtained from DEMNas data processing and land cover data was obtained from manual digitizing of Google Earth's High-Resolution Satellite Imagery data. Data processing uses ArcMap software with scoring and overlay techniques. The results showed that the Kenali Kecil watershed had a dendritic pattern with an area of 15.68 km2 and located in 5 villages, namely: Bagan Pete, Kenali Besar, Penyengat Rendah, Mendalo Darat and Pematang Gajah. The basic rainfall of the Kenali Kecil watershed is 204.21 mm, the slope is mostly >4% and the land cover is mostly residential. Based on the SNI 8197:2015 procedure and the results of the scoring and overlay process with ArcMap, the flood susceptibility level of the Kenali Kecil watershed is at a medium hazard level of 8.25 km2 (52.6%) and a height of 7.43 km2 (47.4%).